Nietzsche contra Nietzsche: linguagem, história e política. Um estudo sobre a Segunda Consideração Intempestiva (1874) - Biasutti, Rusley Breder (2018)
In 1874, following his project of publishing a series of short texts under the general title of Untimely Meditations, the German philosopher Friedrich Nietzsche published the second of the them, subtitled On the uses and disadvantages of history for life. Although the reception of the work was not significant among the German historians of the period, in it, the philosopher, imbued with his characteristic style of belligerent writing, defers an attack on the project of formation of a historical science that was being carried out by prominent figures of the German historiographical tradition. Despite Nietzsche's clear notes and criticisms of the historiographical culture of his time, surprisingly, there are still few papers that examine in detail the author's historical thinking; and when they do, such works tend to consider its philosophical or epistemological aspect much more than its historical content, disregarding the locus of production of the work. Thus, the thesis that guides our work is that the considerations of the Second Untimely Meditation cannot be understood without considering the historical context and the political culture in which the work was produced. Only the analysis of the political and cultural background allows us to re-address the questions that Nietzsche actually had in mind when writing the work. In doing so, we intend to demonstrate that, rather than an attack on the formation of German historical science, the Second Untimely Meditation must be understood as a reflection of the political dimension of historical consciousness and as an attempt to strike the relations that were established between the German State that had just been born in 1870 and the work of historians. What the philosopher intends to combat, then, is an excessive politicization of the past, led by historians in the service of the State, and whose objective was the elaboration of the myths of formation that would guarantee to the young nation the historical legitimacy necessary for the preservation of its unity.